2013
DOI: 10.1080/03601234.2012.716733
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of elements by edible mushroom species: Part I. Problem of trace element toxicity in mushrooms

Abstract: The aim of this study was to evaluate Cd, Co, Cu, Hg, Ni, Pb, Sr and Zn accumulation in six edible mushroom species and to assess their risk and benefits to human consumers. Mushrooms (Leccinium aurantiacum, Xerocomus badius, Lactarius deliciosus, Boletus edulis, Cantharellus cibarius and Suillus luteus) were collected from selected regions of Poland during 1990-2010. The highest diversity between studied mushroom species was observed in terms of Cu and Zn accumulation. Significant differences in the accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 43 publications
5
17
1
Order By: Relevance
“…High concentration of Fe detected in this study is consistent with the observation in the literature of excessive concentration of Fe (2970.6 µg g −1 ) in mushrooms . The mean concentration of Ni ranged from 9.5 ± 3.1 to 35.1 ± 14.1 µg g −1 which is higher than most values reported in the literature, suggesting that mushrooms in the current study are among the most contaminated by Ni. Concentration of xenobiotic metal Pb was higher in A. loosei , A. miomboensis and T. clypeatus than in any other mushroom species in this study (Table ) suggesting that overconsumption of these three species may increase the risk of Pb contamination.…”
Section: Resultssupporting
confidence: 90%
“…High concentration of Fe detected in this study is consistent with the observation in the literature of excessive concentration of Fe (2970.6 µg g −1 ) in mushrooms . The mean concentration of Ni ranged from 9.5 ± 3.1 to 35.1 ± 14.1 µg g −1 which is higher than most values reported in the literature, suggesting that mushrooms in the current study are among the most contaminated by Ni. Concentration of xenobiotic metal Pb was higher in A. loosei , A. miomboensis and T. clypeatus than in any other mushroom species in this study (Table ) suggesting that overconsumption of these three species may increase the risk of Pb contamination.…”
Section: Resultssupporting
confidence: 90%
“…The Hg content in L. deliciosus from Pu’er in Yunnan was similar to the values reported for this mushroom in Europe: Germany (0.35 mg kg −1 dm), Hungary (0.45–0.61 mg kg −1 db), Poland (0.94 ± 0.13 mg kg −1 db) and Spain (0.51–0.77 mg kg −1 db) (Melgar et al 2009; Mleczek et al 2013; Seeger and Nützel 1976; Vetter and Berta 1997). …”
Section: Resultssupporting
confidence: 64%
“…Cd > Cu > Zn > Pb > Mn > Fe The analysis of PF coefficient values demonstrated that mushrooms most effectively accumulated such metals as cadmium, copper and zinc. Other authors obtained similar results [32][33][34].…”
Section: Forests Of the Staporkow Forest Divisionsupporting
confidence: 71%